Application Of The Decision Tree Method As A Factor Causing Students To Drop Out (Case Study: SMK Tunas Pelita Binjai City) - Darma Yanti, Intan; Sihombing, Marto; Prahmana, I Gusti (Devitara Innovations, 2024)
The problem of the phenomenon of dropping out of school for students at the Senior High School or Vocational Education level is increasingly widespread. In fact, education is a very important field to develop the quality of Human Resources (HR) for the country. Ayu et al said that one of the important sectors that directly contributes the most in developing the quality of Human Resources (HR) is the education sector. Meanwhile, SMK Tunas Pelita Binjai is one of the vocational high schools in Binjai City that also faces the problem of dropping out of school. Based on internal school data, in 2023 there are 32 students or around 5% of the total students at SMK Tunas Pelita Binjai who cannot complete their education until the end. This figure is quite high and is a serious concern for the school. Some of the factors such as students' interest in learning have decreased so much that they make students inactive or often alpha, parents with low levels of education tend to lack understanding and appreciation for the importance of formal education for their children's future, they may not have high aspirations for the achievement of children's education, economic impacts that are very binding on the family so that children prefer to work to help the family economy. Seeing the very complex problem of dropping out of school, a comprehensive and systematic approach is needed to analyze what factors are the causes. The application of the Decision Tree method in identifying the factors that cause school dropouts at SMK Tunas Pelita Binjai, is expected to produce new information that can be used as a basis for schools to design more effective strategies and interventions in preventing and reducing school dropout rates. The author uses the help of RapidMiner software to see the factors that cause students to drop out of school by using the C4.5 Decision Tree method to create a decision tree from existing student data. So that from the RapidMiner calculation process, it can be concluded that what are the factors that cause the student to drop out of school.